An unusual branching pattern of common and external carotid artery in a human cadaver: a case report - Kishve, Prajakta S (Australasian Medical Journal, 2011)
During a routine dissection in the Department of Anatomy of the Rural Medical College, Loni, we found a rare variation in branching pattern of the common carotid artery (CCA) and external carotid artery (ECA) bilaterally. The knowledge of possible anatomical variations of CCA and ECA are especially important in the surgeries of head, neck and face; and also for the radiologist to understand and interpret carotid system imaging when undertaking cerebral angiography. This case and the clinical significance of this variation are reported in this paper.